2016
DOI: 10.1534/g3.116.034165
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of alin-42/periodNull Allele Implicates All Three Isoforms in Regulation ofCaenorhabditis elegansMolting and Developmental Timing

Abstract: The Caenorhabditis elegans heterochronic gene pathway regulates the relative timing of events during postembryonic development. lin-42, the worm homolog of the circadian clock gene, period, is a critical element of this pathway. lin-42 function has been defined by a set of hypomorphic alleles that cause precocious phenotypes, in which later developmental events, such as the terminal differentiation of hypodermal cells, occur too early. A subset of alleles also reveals a significant role for lin-42 in molting; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…The largest isoform, B, contains sequence found in both the A and C isoforms ( Figure 2D ). Work in other labs has suggested that the LIN-42A and B isoforms are of greater functional importance than LIN-42C ( Tennessen et al 2006 ; Monsalve et al 2011 ; Edelman et al 2016 ). Using an antibody developed against the C terminal region of LIN-42 , we were able to clearly visualize the LIN-42A isoform ( Figure 2E , Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest isoform, B, contains sequence found in both the A and C isoforms ( Figure 2D ). Work in other labs has suggested that the LIN-42A and B isoforms are of greater functional importance than LIN-42C ( Tennessen et al 2006 ; Monsalve et al 2011 ; Edelman et al 2016 ). Using an antibody developed against the C terminal region of LIN-42 , we were able to clearly visualize the LIN-42A isoform ( Figure 2E , Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…LIN-42 has 3 isoforms ( Figure 2D ) ( Edelman et al 2016 ). The largest isoform, B, contains sequence found in both the A and C isoforms ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to size, adsl-1(∆) also displays a strong delay during post-embryonic development. In C. elegans progression through larval stage and molting cycles is highly regulated, involving oscillations of LIN-42, the orthologue the circadian protein PERIOD (Monsalve et al 2011;Edelman et al 2016;reviewed in Monsalve and Frand, 2012). The developmental changes associated with this progression involve a tight coordination of different cell lineages across the worm's body, and are very well characterized, as are the genetic pathways involved (reviewed in Rougvie and Moss, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to size, adsl-1(∆) also displays a strong delay during post-embryonic development. In C. elegans progression through larval stage and molting cycles is highly regulated, involving oscillations of LIN-42, the orthologue the circadian protein PERIOD [43,44], reviewed in [45]. The developmental changes associated with this progression involve a tight coordination of different cell lineages across the worm's body, and are very well characterized, as are the genetic pathways involved (reviewed in [46]).…”
Section: Discussionmentioning
confidence: 99%